2006
DOI: 10.1111/j.1365-2036.2006.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography: a valid alternative to biopsy in patients with chronic liver disease

Abstract: SUMMARY BackgroundTransient elastography is a novel and non-invasive technique for the evaluation of fibrosis in chronic liver disease. Few studies that exist value the efficacy of transient elastography, mainly in hepatitis C virusinfected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 23 publications
5
46
0
1
Order By: Relevance
“…Optimal cut-off values for significant fibrosis in patients with CHC (stage of fibrosis ≥ 2) have been reported to range from 7.1 to 8.7 KPa (4-7). This range is consistent with our data (37).…”
Section: Strategies and Evidencesupporting
confidence: 83%
See 1 more Smart Citation
“…Optimal cut-off values for significant fibrosis in patients with CHC (stage of fibrosis ≥ 2) have been reported to range from 7.1 to 8.7 KPa (4-7). This range is consistent with our data (37).…”
Section: Strategies and Evidencesupporting
confidence: 83%
“…Currently, there are insufficient data to enable the reliability of assessments of mild hepatic fibrosis in HCV-infected patients using TE to be determined accurately (4)(5)(6)(7)19,37).…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Knowing that malignant tissues are generally harder than normal surrounding tissue, elastography might provide interesting clinical information to help distinguish benign from malignant tissue based on their specific tissue consistency. Clinical research has shown promising results in differentiating between benign and malignant tissue in the thyroid gland [5] , breast [6][7][8] , prostate [9,10] and to assess liver fibrosis [11][12][13][14] . Recently, elastography has also been introduced during EUS examination [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an increasing need for alternative noninvasive methods to estimate the stage of liver fibrosis [12][13][14][15][16][17][18][19][20][21] . Transient elastography and real-time tissue elastography are recently developed technologies, which are safe and noninvasive techniques to evaluate fibrosis in chronic liver disease.…”
mentioning
confidence: 99%